Além das quatro linhas: estudo sobre a trajetória profissional de jovens atletas do futebol - Guimaraes, Arthur Silveira (2012)
The relationship between sport and society is on a topic of great relevance to studies of social sciences. This proposal is to investigate the football. However, realizing this phenomenon related to the issue of professional projection, considering that football in Brazil is a project of life for many young people and their families. Although this work presents professional football as a starting point, the focus of research is not professional sports and high level performance. The proposal is directed to the moment of transition between amateur football and professional football. Focus will be on the way in which children become professionals in the called “world of the ball”. From the trajectories of young athletes, this work attempts to present the nuances in the production of soccer players to the market of the ball. The survey was conducted in Auto Esporte Clube, college sports located in João Pessoa-PB. The methodology used for data collection was by conducting a qualitative study, based on the use of individual interviews and using the voice recorder and direct observation with a view to better understand and perceive the environment formed in the athletes.